Capitalist workingman's paradises revisited : corporate welfare work in Great Britain, the USA, Germany and France in the golden age of capitalism, 1880-1930 - Gier, H. G. de (Amsterdam University Press, 2016)
This book offers an in-depth exploration of the international phenomenon of enlightened paternalist capitalism and social engineering in the golden age of capitalism in the United States, United Kingdom, Germany, and France. Erik de Gier shows how utopian socialist, religious, and craft-based ideas influenced the welfare work and educations programmes offered by paternalistic businesses in different ways from nation to nation, looking closely at sites like the Pullman community in Chicago and Port Sunlight in the UK. De Gier brings the book fully up to date with a brief comparison to contemporary welfare capitalism in our highly flexible working world.